European Union against illegal immigration: the institutionalization of hate - Pomares Cintas, Esther (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The passage of time has the virtue of providing an overview of the migration policy of the European Union, without the risk of misunderstandings. The strategy based on an ad hoc design of exclusion-incapacitation spaces as instruments to combat illegal immigration has fostered a culture of hate, which is consubstantial with this communitarian policy model. This paper intends to analyze its different manifestations.
Keywords: Illegal immigration; fundamental human rights; european migration policy; law pragmatism